Preparation method and application of high-density, fast-decay time scintillation crystal Bi2W2O9
By preparing BI2W2O9 flash crystals, specific synthesis and crystal preparation steps are used to solve the problem of longer attenuation of oxide flash crystals, and the flash crystals of high -density and fast attenuation time can be achieved to meet the needs of high -energy detection fields.
Patent Information
- Application Number
- CN202310238466.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-14
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2043-03-14
AI Technical Summary
The decay time of existing oxide scintillation crystals is relatively long, and it is difficult to meet the demand for fast decay time in the high-energy detection field.
By preparing BI2W2O9 flash crystals, specific synthesis and crystal preparation steps are used, including pre -fever preparation, high temperature thermal treatment of mixture, and crystal growth process to control the density and attenuation time of the crystal.
The obtained Bi2W2O9 crystal has high density (density at room temperature is as high as 8.84g/cm3) and fast decay time (minimum decay time is around 1.40ns), meeting the needs of high-energy detection and protection.
Smart Images

Figure CN116200829B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of scintillation crystal materials, and in particular relates to a preparation method and application of a scintillation crystal Bi2W2O9 with high density and fast decay time. Background Art
[0002] The detection and protection of high-energy rays (X-rays, gamma rays, etc.) and particles (neutrons, beta particles, etc.) are of great significance in modern society, and this importance is also increasing rapidly with the rapid development of technologies such as nuclear medicine testing and diagnosis, high-energy physics experiments, and freight safety supervision.
[0003] Scintillating crystals refer to functional crystal materials that can convert the energy of high-energy rays or high-energy particles into fluorescent pulses in the ultraviolet or visible light band. Since NaI:Tl was discovered as a scintillating crystal and put into practical use, researchers have discovered and proposed many excellent scintillating crystals. At present, practical scintillating crystals are mainly divided into two categories: oxide crystals and halide crystals. Among them, oxide crystals are mainly Bi4Ge3O 12 (BGO), PbWO4(PWO), CdWO4(CWO), Lu 2-x Y x Crystals such as SiO5:Ce (LYSO:Ce) are representative, with advantages such as high density, good stability, and strong radiation resistance. Halide crystals are represented by crystals such as NaI:Tl, SrI2:Eu, and LaBr3:Ce, which have advantages such as high light yield, short decay time, and high energy resolution. In recent years, the continuous development of the field of high-energy detection has put forward new and higher requirements on the performance of scintillation crystals. The three most important indicators for measuring the performance of scintillation crystals are light yield, energy resolution, and fluorescence decay / response time. Scintillating crystals with high light yield, high energy resolution of less than 3.0%, and picosecond time resolution are the future development direction.
[0004] As mentioned above, compared with halide crystals, oxide crystals have high density and strong radiation resistance, but the decay time is generally above 100ns or even in microseconds or milliseconds. For example, the decay time of BGO crystal is about 317ns, the decay time of CWO is as high as 12.7μs, and the decay time of LYSO:Ce crystal is less than 100ns, but it also reaches about 42ns. PWO crystals (~6ns), YAG:Yb crystals (~2.5ns), and YAP:Yb crystals (~1.5ns) have shorter decay times, but the light yields of these crystals are generally very low, and the presence of Pb elements in the crystals will also pose a very serious threat to the environment. Therefore, how to effectively shorten the decay time of oxide crystals and improve crystal quality is a technical problem that needs to be solved urgently. Summary of the invention
[0005] The present invention aims to solve the problems existing in the prior art and provides a method for preparing and applying a scintillation crystal Bi2W2O9 with high density and fast decay time. The room temperature density of the obtained crystal is as high as 8.84g / cm 3 The minimum decay time is around 1.40ns, which can meet the usage requirements in various fields.
[0006] In order to achieve the above technical objectives, the technical solution adopted by the present invention is:
[0007] A method for preparing a high-density, fast-decaying-time scintillation crystal Bi2W2O9 comprises the following preparation steps:
[0008] (1) Synthesis and seed crystal preparation of Bi2W2O9: Li2CO3 and H3BO3 are mixed thoroughly and uniformly, pressed into blocks on a tablet press, placed in a crucible and slowly heated to 390-410°C for 24 hours, ground after cooling, pressed into blocks again, heated at 390-410°C for 24 hours, and then cooled to obtain Li2B4O7 pre-sintered material; Bi2O3, WO3 and Li2B4O7 pre-sintered materials are fully mixed, placed in a crucible and heated to 850-950°C for 10 hours, cooled to 690-710°C within 24 hours, and then poured into a ceramic disc for rapid cooling, and cooled to room temperature to obtain a cooling material; the cooling material is subjected to basic crushing treatment, then pickled with dilute hydrochloric acid, then washed with ultrapure water, filtered and dried to obtain tiny grains of Bi2W2O9, i.e., Bi2W2O9 seed crystals; small grains with complete morphology and high transparency are selected as seed crystals;
[0009] (2) Determine the saturation temperature: Mix Li2CO3 and H3BO3 thoroughly and evenly, press them into blocks on a tablet press, place them in a crucible and slowly heat them to 390-410°C for 24 hours; after cooling, grind them, press them into blocks again, heat them at 390-410°C for 24 hours, and then cool them down. Repeat the grinding, pressing and sintering process 2-5 times to obtain Li2B4O7 pre-sintered material; mix Bi2O3, WO3 and Li2B4O7 pre-sintered material, place them in a crucible, and ignite them with oxygen above the crucible. After the alumina thermal insulation fiber tube is well insulated, it is heated to 850-950°C, kept at a constant temperature for 24-48 hours, and then cooled to 825-835°C to obtain a mixed solution; the Bi2W2O9 seed crystal obtained in the fixed step (1) is slowly lowered to 2 cm above the liquid surface of the mixed solution, and after staying for 10 minutes, it is slowly lowered to make the Bi2W2O9 seed crystal touch the liquid surface, and the seed crystal is taken out after 2 hours, and the temperature is repeatedly adjusted to test and observe the surface of the seed crystal until the temperature at which crystals appear on the surface is the saturation temperature T, and the control deviation does not exceed 2°C;
[0010] (3) Crystal growth: The mixed solution obtained in step (2) is heated again to 850-950°C and maintained at this temperature for 10 hours to completely dissolve any Bi2W2O9 impurity crystals that may be produced; then the mixture is cooled to 2°C above the saturation temperature T, and a Bi2W2O9 seed crystal is slowly introduced so that it lightly touches the liquid surface; the mixture is cooled to the saturation temperature T for 2 hours, and then the mixture is cooled at a rate of 0.01-0.05°C / h to about 20°C below the saturation temperature T to allow crystal growth; after growth is completed, the crystal is lifted from the liquid surface and cooled to room temperature for 48 hours to obtain a Bi2W2O9 crystal. The Bi2W2O9 crystal obtained in this step can be used to cut the seed crystal required for the preparation step (2).
[0011] Furthermore, in step (1), the molar ratio of Li2CO3, H3BO3, Bi2O3 and WO3 is 1:4:1:3.
[0012] Furthermore, the crucible in step (1) and step (2) is a platinum crucible.
[0013] Furthermore, the molar ratio of Li2CO3, H3BO3, Bi2O3 and WO3 in step (2) is 1:4:1:3; the molar amount of Li2CO3, H3BO3, Bi2O3 and WO3 in step (2) can be determined according to the actual target crystal size required.
[0014] Furthermore, in step (2), the Bi2W2O9 seed crystal obtained in step (1) is fixed with platinum wire.
[0015] Furthermore, in step (3), the crystal growth cycle is 10-40 days, and the crystal rotation rate is controlled at 10-40 r / min.
[0016] Furthermore, in step (3), the crystal rotation rate is controlled at 15-25 r / min.
[0017] The invention discloses an application of a method for preparing a high-density, fast-decaying-time scintillation crystal Bi2W2O9. The obtained crystal is used in the technical fields of detection and protection of high-energy rays and high-energy particles.
[0018] The main research direction is high-density, high-light-yield, fast-decay-time oxide crystals. This invention organically combines the heaviest stable element Bi and heavy element W in the periodic table with the low-dimensional Aurivillius crystal structure, and proposes Bi2W2O9 as a new generation of high-density, fast-decay-time scintillation crystal materials. In the Aurivillius structure, [Bi2O2] 2+ Fluorite-like structure layer and [W2O7] 2-The perovskite-like layers are effectively stacked in three-dimensional space, allowing Bi and W to effectively occupy space to a greater extent, obtaining a large crystal density and high radiation cutoff capability. At the same time, the low-dimensional layered structure makes the Bi2W2O9 crystal have strong dielectric confinement and quantum confinement effects, and the exciton binding energy is very high, which reduces the probability of non-radiative recombination and effectively reduces the decay time, thereby obtaining a new type of scintillating crystal material with high density and fast decay time.
[0019] The Bi2W2O9 crystal provided by the present invention can be used as a high-density, fast scintillation time scintillation crystal for the detection of high-energy rays and high-energy particles. It can be used in, but not limited to, time-of-flight technology-based positron emission tomography (TOF-PET) equipment, calorimeters for high-energy physics experiments, environmental radiation level monitors, and security inspection equipment at transportation sites such as airports and train stations.
[0020] The Bi2W2O9 crystal prepared by the method of the present invention can be used as an intrinsic luminescent scintillator, and Ce can be added during crystal growth. 3+ , Yb 3+ Rare earth ions such as fluorescein can be used as non-intrinsic luminescent scintillators to optimize the energy level structure and increase the light yield.
[0021] The Bi2W2O9 prepared by the method of the present invention can be made into composite materials with glass, resin, rubber, fiber, etc., and used for the protection of high-energy rays and high-energy particles, such as human radiation shielding clothing, gamma-ray shielding and other application fields.
[0022] At the same time, the present invention provides a method for synthesizing Bi2W2O9 seed crystals, that is, Bi2W2O9 particles or powders, which can obtain Bi2W2O9 particles and powders with a purity of 99.9% or above, which are used in but not limited to the field of radiation shielding and protection.
[0023] The present invention provides a method for growing Bi2W2O9 crystals, which can obtain Bi2W2O9 crystals of centimeter level or larger in size. The crystals have good transparency and no macro cracks, and can meet the requirements for characterization and application of scintillation crystals.
[0024] Beneficial Effects
[0025] (1) The Bi2W2O9 crystal prepared by the present invention has a room temperature density of up to 8.84 g / cm3 and an effective atomic number of 76, which is higher than that of PWO crystal. It has a strong blocking ability against high-energy rays and particles such as X-rays and gamma rays and can be used as a radiation shielding and protection material;
[0026] (2) The Bi2W2O9 crystal prepared by the present invention has two fluorescence emission peaks in the optical transmittance range of 400-500nm, and still has strong fluorescence emission under X-ray excitation, and the emission peak is located within the optical transmittance range of the crystal, and the self-absorption is small; this emission band can achieve a good match with the mature photomultiplier device PMT / SiPM;
[0027] (3) The decay time of the Bi2W2O9 crystal prepared by the present invention is about 1.40ns, and the slow component is 41.63ns. However, the slow component only contributes 2% of the decay time, which is an ultrafast decay scintillator.
[0028] (4) The Bi2W2O9 synthesis method provided by the present invention uses raw materials that can be purchased on the market at a low price, does not contain toxic or harmful elements, and is easy to carry out large-scale production;
[0029] (5) The synthesis method of Bi2W2O9 provided by the present invention requires conditions that are easy to achieve and the operation is simple. Centimeter-sized Bi2W2O9 crystals can be obtained. The crystals have high transparency and can be used for crystal orientation, scintillation performance testing and scintillation device design applications. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 A comparison diagram of the X-ray diffraction spectrum of the Bi2W2O9 seed crystal synthesized in Example 1 of the present invention and the theoretical fitting spectrum;
[0031] Figure 2 This is a picture of a centimeter-level single crystal of Bi2W2O9 grown in Example 2 of the present invention;
[0032] Figure 3 This is the emission spectrum of the Bi2W2O9 crystal of the present invention;
[0033] Figure 4 is a fluorescence attenuation curve diagram of the Bi2W2O9 crystal of the present invention;
[0034] Figure 5 Schematic diagram of the basic structure of a scintillation device based on Bi2W2O9 crystal. DETAILED DESCRIPTION
[0035] The technical solution of the present invention is further described below in conjunction with specific embodiments, but is not limited thereto.
[0036] Example 1
[0037] Bi2O3, WO3, Li2CO3 and H3BO3 are used as raw materials. 0.1 mol Li2CO3 and 0.4 mol H3BO3 are completely mixed and pressed into blocks on a tablet press, and then slowly heated to 400℃ and kept at a constant temperature for 24 hours in a platinum crucible. After cooling down, they are ground and pressed into blocks again, and then heated at 400℃ for 24 hours and then cooled down to obtain Li2B4O7 pre-sintered materials. After 0.1 mol Bi2O3, 0.3 mol WO3 and Li2B4O7 pre-sintered materials are fully mixed, placed in a platinum crucible and heated to 900℃ and kept at a constant temperature for 10 hours, cooled down to 700℃ within 24 hours, and then poured into a ceramic disc for rapid cooling. The cooled materials are basically crushed, pickled with dilute hydrochloric acid, and then washed with ultrapure water, filtered and dried to obtain tiny grains of Bi2W2O9. The obtained tiny Bi2W2O9 grains were ground and then subjected to powder X-ray diffraction test. The diffraction pattern was in good agreement with the theoretical diffraction pattern based on the Bi2W2O9 crystal structure fitting, as shown in the attached figure. Figure 1 As shown, it is proved that Bi2W2O9 is obtained by the method of Example 1.
[0038] Example 2
[0039] Bi2O3, WO3, Li2CO3 and H3BO3 are used as raw materials. 1 mol Li2CO3 and 4 mol H3BO3 are thoroughly mixed and pressed into blocks on a tablet press, and then slowly heated to 400℃ and kept at a constant temperature for 24 hours in a platinum crucible. After cooling down, grind, press into blocks again, and heat at 400℃ for 24 hours before cooling down. Repeat grinding, tableting and sintering at 400℃ for 3 times to obtain Li2B4O7 pre-sintered material. After 1 mol Bi2O3, 3 mol WO3 and Li2B4O7 pre-sintered material are fully mixed, they are placed in a platinum crucible, and after insulation is done with an alumina insulation fiber tube above the platinum crucible, they are heated to 850℃ and kept at a constant temperature for 24 hours, and then heated to 900℃ and kept at a constant temperature for 10 hours. Cool down to about 830℃, fix the Bi2W2O9 seed crystal with platinum wire and slowly lower it to 2cm above the liquid surface. After staying for 10 minutes, slowly lower it so that the seed crystal touches the liquid surface. Take out the seed crystal after 2h, and observe whether the surface of the seed crystal dissolves or grows. In this way, the saturation temperature T can be accurately determined with a deviation of no more than 2℃. After determining the saturation temperature T, keep the solution at 900℃ for 10h again to completely dissolve any Bi2W2O9 impurity crystals that may be produced. Then cool down to 2℃ above the saturation temperature T, and slowly lower the Bi2W2O9 seed crystal so that it touches the liquid surface. Cool down to the saturation temperature T in 2h, and then cool down to about 20℃ below the saturation temperature at a rate of 0.01-0.05℃ / h. Lift the crystal from the liquid surface and cool it to room temperature in 48h to obtain a Bi2W2O9 single crystal, as shown in the attached Figure 2 shown.
[0040] Example 3
[0041] The fluorescence emitted by the scintillating crystal under the excitation of high-energy rays / particles should be within the sensitive range of the photomultiplier tube PMT or the silicon photomultiplier device SiPM. Based on the Bi2W2O9 single crystal grown in Example 2, the fluorescence emission spectrum of the Bi2W2O9 crystal was measured using a steady-state / transient fluorescence spectrometer. Figure 3 As shown in the figure, Bi2W2O9 has a wide emission band between 400-600nm, which is just in the sensitive range of PMT and SiPM, meeting the requirements of the luminescence band of scintillation crystals.
[0042] Example 4
[0043] The decay time of the luminescence of the scintillation crystal under the excitation of high-energy rays / particles is an important parameter for ultrafast scintillation crystals. Based on the Bi2W2O9 single crystal grown in Example 2, the fluorescence decay curve of the Bi2W2O9 crystal was measured. Figure 4 As shown in the figure, Bi2W2O9 exhibits a three-exponential decay characteristic, with a fast component of 1.40ns, contributing 78% of the fluorescence decay lifetime; another fast component of 5.22ns, contributing 20% of the fluorescence decay time; and a slow component of 41.63ns, but only contributing 2% of the fluorescence decay lifetime. Therefore, Bi2W2O9, as an ultrafast scintillation crystal, exhibits extremely fast fluorescence decay characteristics.
[0044] Example 5
[0045] Similarly, based on the Bi2W2O9 crystal grown in Example 2, a 10mm×10mm×5mm sample was cut, the end face was polished, and the side face was roughened. One end face was coupled to the photomultiplier tube PMT using silicone grease. The crystal and PMT were sealed in a dark box, and the other end face of the crystal was irradiated by the radiation source. After the Bi2W2O9 scintillates and emits light, the signal is processed by the PMT and the back-end electronic system, and the information carried in the high-energy rays can be analyzed and processed. The basic structure of the scintillation detection device is shown in the attached figure. Figure 5 shown.
[0046] It should be noted that the above embodiments are only partial embodiments of the preferred methods of implementing the present invention, rather than all embodiments. Obviously, based on the above embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.
Claims
1. A method for preparing a high-density, fast-decaying-time scintillation crystal Bi2W2O9, characterized in that: The method comprises the following preparation steps: (1) Synthesis and seed crystal preparation of Bi2W2O9: Li2CO3 and H3BO3 were mixed evenly, pressed into blocks, placed in a crucible and heated to 400 o C for 24 h, then cooled and ground, pressed into blocks again, and heated at 400 o C for 24 h and then cooled to obtain Li2B4O7 pre-sintered material; Bi2O3, WO3 and Li2B4O7 pre-sintered material were fully mixed and placed in a crucible and heated to 900 o After maintaining the temperature for 10 h, the temperature was lowered to 700 °C within 24 h. o C, and then cooled to room temperature to obtain a cooling material; the cooling material is crushed, then pickled with dilute hydrochloric acid, then washed with ultrapure water, filtered and dried to obtain tiny crystals of Bi2W2O9; small crystals with complete morphology and high transparency are selected as seed crystals; (2) Determine the saturation temperature: Mix Li2CO3 and H3BO3 evenly, press them into blocks, place them in a crucible and heat them to 400 o C for 24 h; after cooling, grind, press into blocks again, and heat at 400 o C for 24 h and then cooled down. The grinding, pressing and sintering process was repeated for 3 times to obtain Li2B4O7 pre-sintered material. Bi2O3, WO3 and Li2B4O7 pre-sintered material were mixed and placed in a crucible. After the crucible was kept warm, it was heated to 850 o C, constant temperature for 24h, cooling to 830 o C, to obtain a mixed solution; the Bi2W2O9 seed crystal obtained in step (1) is slowly lowered to 2 cm above the liquid surface of the mixed solution, and after staying for 10 minutes, it is slowly lowered to make the Bi2W2O9 seed crystal touch the liquid surface. After 2 hours, the seed crystal is taken out, and the temperature is repeatedly adjusted to conduct the test and observe the surface of the seed crystal until the temperature at which crystals appear on the surface is the saturation temperature T; (3) Crystal growth: The mixed solution obtained in step (2) was heated to 900°C again, kept at this temperature for 10 h, and then cooled to 2°C above the saturation temperature T. o C, slowly put Bi2W2O9 seed crystals into the liquid surface to make them touch the liquid surface; cool down to the saturation temperature T for 2 h, and then o C / h rate to 20±5 below the saturation temperature T o C for crystal growth; after the growth is completed, the crystal is lifted from the liquid surface and cooled to room temperature for 48 hours to obtain Bi2W2O9 crystal; The molar ratio of Li2CO3, H3BO3, Bi2O3 and WO3 in step (1) and step (2) is 1:4:1:
3.
2. The method for preparing the high-density, fast-decaying-time scintillation crystal Bi2W2O9 according to claim 1, characterized in that: The crucible in step (1) and step (2) is a platinum crucible.
3. The method for preparing the high-density, fast-decaying-time scintillation crystal Bi2W2O9 according to claim 1, characterized in that: Step (2) fix the Bi2W2O9 seed crystal obtained in step (1) with a platinum wire.
4. The method for preparing the high-density, fast-decaying-time scintillation crystal Bi2W2O9 according to claim 1, characterized in that: The crystal growth cycle in step (3) is 10-40 days, and the crystal rotation rate is controlled at 10-40 r / min.
5. The method for preparing the high-density, fast-decaying-time scintillation crystal Bi2W2O9 according to claim 4, characterized in that: In step (3), the crystal rotation rate is controlled at 15-25 r / min.
6. An application of the method for preparing the high-density, fast-decaying-time scintillation crystal Bi2W2O9 according to any one of claims 1 to 5, characterized in that: The obtained crystals are used in the field of detection and protection of high-energy rays and high-energy particles.
Citation Information
Patent Citations
Photoluminescent crystal material bismuth-europium tungstate and preparation method for same
CN102559180A
Flux growth method and application of large-size bismuth tungstate crystal
CN114561704A